THE EFFECT OF WUDHU AND DZIKIR THERAPY ON THE LEVEL OF INSOMNIA IN THE ELDERLY - USWATUN HASANAH; RAHMAT KURNIAWAN; NURLINA HAYUN PADILA (Sekolah Tinggi Ilmu Kesehatan Widya Dharma Husada Tangerang, 2022)
ABSTRACTThe population census in 2020 noted that the number of elderly people in Indonesia reached 26.82 million people (9.92%) of the population. The prevalence of insomnia in the elderly in Indonesia is quite high, around 67%. Management of insomnia, broadly divided into two, pharmacological and non-pharmacological. The non-pharmacological therapies used in this study are hygiene (ablution) and mindfulness (dhikr). The purpose of this study was to determine whether there was an effect of giving ablution and dhikr therapy on the level of insomnia in the elderly in the RT 002/007 area of Gang Langgar Kalideres, West Jakarta. The research method uses experimental quantitative methods with a one group pre-post test design approach, this study reveals a causal relationship by involving one group of subjects. The subject group was observed before the intervention, then observed again after the intervention. The measuring instrument in this study used the KSPBJ-IRS questionnaire and checklist sheet. The research sample used the Non-Probability Sampling (Purposive Sampling) method. Data analysis using Wilcoxon test. The results of the study were ages 55-64 (88%), female gender (64%), widowed/widow status (52%), elementary school education (80%). The p-value = 0.000 (<0.05) the mean difference is 4.92. The conclusion is that there is an effect of ablution and dhikr therapy on the level of insomnia in the elderly. It is hoped that this research can increase knowledge about how to deal with insomnia with non-pharmacological methods so that the level of insomnia is reduced and the health of the elderly is increased. Keywords: Dzikir, Elderly, Insomnia, Wudhu PENGARUH TERAPI WUDHU DAN DZIKIR TERHADAPTINGKAT INSOMNIA PADA LANSIA ABSTRAKSensus penduduk tahun 2020 mencatat jumlah lansia di Indonesia mencapai 26,82 juta jiwa (9,92%) dari populasi. Prevalensi insomnia lansia di Indonesia tergolong tinggi sekitar 67%. Penatalaksanaan insomnia, secara garis besar dibagi menjadi dua, farmakologi dan non-farmakologi. Terapi non-farmakologi yang digunakan dalam penelitian ini yaitu hygienitas (wudhu) dan mindfulness (dzikir). Tujuan penelitian ini adalah untuk mengetahui apakah ada pengaruh dari pemberian terapi wudhu dan dzikir terhadap tingkat insomnia pada lansia di Wilayah RT 002/007 Gang Langgar Kalideres, Jakarta Barat. Metode penelitian menggunakan metode kuantitatif eksperimen dengan pendekatan one group pra-post test design, penelitian ini mengungkapkan hubungan sebab akibat dengan melibatkan satu kelompok subjek. Kelompok subjek diobservasi sebelum dilakukan intervensi, kemudian diobservasi lagi setelah dilakukan intervensi. Alat ukur pada penelitian ini menggunakan kuesioner KSPBJ-IRS dan lembar checklist. Sampel penelitian menggunakan metode Non-Probability Sampling (Purposive Sampling). Analisa data menggunakan uji Wilcoxon. Hasil penelitian usia 55-64 (88%), jenis kelamin perempuan (64%), status duda/janda (52%), pendidikan SD (80%). Nilai p-value = 0,000 (< 0,05) selisih mean 4,92. Kesimpulan ada pengaruh terapi wudhu dan dzikir terhadap tingkat insomnia pada lansia. Saran diharapkan penelitian ini dapat menambah pengetahuan mengenai bagaimana cara mengatasi insomnia dengan non-farmakologi agar tingkat insomnia berkurang dan kesehatan lansia meningkat. Kata kunci: Dzikir, Insomnia, Lansia, Wudhu